Preparation method of special carbon nanotube fiber for high-performance photovoltaic screen

By treating carbon nanotubes with hydrogen peroxide, potassium permanganate aqueous solution and polytetrafluoroethylene, combined with dry-spray wet spinning and electroplating technology, the problems of uneven distribution, poor ductility and insufficient interface binding during the silk screen printing process are solved. The obtained special carbon nanotube fibers have high strength and good adhesion, achieving clear and stable printing and efficient conversion of photovoltaic screens.

CN119593110APending Publication Date: 2025-03-11KUNSHAN LEBANG PRECISION TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411852159.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing carbon nanotube fibers are difficult to be uniformly distributed during the silk screen printing process, have poor ductility, and insufficient interface bonding with mesh substrates, resulting in poor printing accuracy and consistency, high cost, and difficult to apply on a large scale.

Method used

By immersing the carbon nanotubes in hydrogen peroxide and potassium permanganate aqueous solution, and then immersing them in polytetrafluoroethylene, the purity and surfactivity sites of the carbon nanotubes are improved, combined with dry-spray wet spinning technology, gravity is used to adjust the orientation of the carbon nanotubes, and the strength and adhesion of the fibers are improved through electroplating and plasma treatment.

Benefits of technology

The obtained special carbon nanotube fiber has high strength, good adhesion and surface smoothness, which can achieve clear and stable printing, improve the stability and conversion efficiency of photovoltaic screens, reduce manufacturing costs, and is suitable for large-scale commercial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119593110A_ABST
    Figure CN119593110A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a special carbon nanotube fiber for a high-performance photovoltaic screen printing plate, which comprises the following steps: adding a carbon nanotube into a mixed solution of hydrogen peroxide and potassium permanganate, then adding a polytetrafluoroethylene emulsion, magnetically stirring, filtering, drying, adding a chlorosulfonic acid solution, magnetically stirring, and filtering to obtain the special carbon nanotube fiber for the high-performance photovoltaic screen printing plate. Injecting into an air extrusion spinning solution trickle along the vertical direction, entering a butanone coagulating bath, stretching by a coiling and winding device, collecting, soaking in ethanol, filtering, drying in vacuum, and coating a film on the surface to obtain the special carbon nanotube fiber. The prepared fiber is high in strength, high in adhesion and smooth in surface, is particularly suitable for being used for preparing a silk-screen printing plate, and is clear and stable in printing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a carbon nanotube fiber, and more specifically, to a method for preparing a special carbon nanotube fiber for high-performance photovoltaic screens. Background Art

[0002] As people pay more attention to clean energy, photovoltaic cells are developing rapidly. The metallization process of photovoltaic cells usually uses screen printing technology to form the positive and negative electrodes of the battery. The screen printing screen is generally made of mesh cloth, steel mesh, polyimide film, etc., which are bonded layer by layer by hot melt adhesive. The use process is to apply pressure on the slurry end of the screen with a scraper and move toward the other end of the screen, so that the conductive slurry containing metal is squeezed from the mesh holes onto the substrate. The lower the wire diameter of the mesh, the lower the unit consumption and the lower the cost. This requires the mesh of the photovoltaic screen to have the characteristics of high mesh count, low wire diameter, high strength and high toughness. At present, the mesh of photovoltaic printing screens is mostly polyester, stainless steel, tungsten steel and nickel. After the wire diameter of these materials reaches a certain level, the strength, toughness and stability are difficult to guarantee, and the life is short, which cannot meet the increasingly high requirements of the photovoltaic printing industry - lower line width, longer life and lower unit consumption. At present, the photovoltaic screen has developed to the third generation. The use of carbon nanotube fiber to prepare the mesh of the photovoltaic screen can better improve the stability and conversion efficiency of the photovoltaic screen. However, there are several problems in the existing preparation of carbon nanotube fiber, which makes it impossible to apply it on a large scale commercially. Due to the above technical bottlenecks, its application potential has not been fully released.

[0003] First, carbon nanotube fibers are usually harder and less flexible than traditional fibers due to their high strength and high modulus properties. In the screen printing process, the fibers are required to be evenly distributed on the mesh and maintain a certain arrangement order, which is more difficult for carbon nanotube fibers because they may tend to aggregate or produce non-uniform distribution, affecting printing accuracy and consistency. Screen printing meshes require a certain degree of flexibility and ductility to adapt to tension changes and deformation during printing. Although carbon nanotube fibers are extremely strong, their ductility is generally poor, which may cause the mesh to break easily or deform irreversibly when subjected to force, affecting the service life and printing quality. How to firmly fix the carbon nanotube fibers to the mesh substrate is also a challenge. Traditional adhesives may not be sufficient to provide sufficient interfacial bonding force, especially in printing environments that require high temperature resistance and chemical resistance. Therefore, it is necessary to ensure a stable connection between the fiber and the substrate. The production cost of high-quality carbon nanotube fibers is relatively high, and using them for screen printing meshes may significantly increase manufacturing costs, limiting their widespread application. In addition, it is also a major problem to mass-produce carbon nanotube fibers and maintain consistent performance to ensure stable performance during long-term use and different environments during the screen printing process.

[0004] Therefore, how to provide a preparation method for special carbon nanotube fibers with high strength, high adhesion, solvent resistance, smooth surface, clear and stable printing has high application value. Summary of the invention

[0005] In order to solve the problems of high strength, high adhesion and smoothness of carbon nanotube fibers, the present application provides a method for preparing special carbon nanotube fibers for high-performance photovoltaic screens.

[0006] The present application provides a method for preparing special carbon nanotube fibers for high-performance photovoltaic screens, comprising the following steps: S1: adding carbon nanotubes to a mixed solution of hydrogen peroxide and potassium permanganate, then adding polytetrafluoroethylene emulsion, magnetically stirring, filtering, and drying to obtain pretreated multi-walled carbon nanotubes, then adding chlorosulfonic acid solution to the pretreated carbon nanotubes, magnetically stirring, to obtain a carbon nanotube liquid crystal spinning solution; S2: injecting the carbon nanotube liquid crystal spinning solution prepared in S1 into the air in a vertical direction to extrude a thin stream of the spinning solution, and then entering the butanone coagulation bath, and stretching the spinning solution by a winding device, collecting the spinning solution, and then immersing the spinning solution in ethanol, filtering, and vacuum drying to obtain carbon nanotube fibers; S3: coating the surface of the carbon nanotube fiber obtained in S2 to obtain special carbon nanotube fiber.

[0007] By adopting the above scheme, the carbon nanotubes are immersed in hydrogen peroxide, potassium permanganate aqueous solution and then immersed in polytetrafluoroethylene for protonation treatment, which improves the purity of the carbon nanotubes, reduces their agglomeration, introduces active functional groups such as hydroxyl groups, increases surface active sites, and makes the carbon nanotubes more tightly combined with the spinning liquid matrix. The obtained fiber has good strength performance, a smoother surface, and the obtained photovoltaic screen printing is clear and stable. This application adopts dry-wet spinning, which first extrude the spinning liquid into the air and apply gravity stretching, and then immerse it in a coagulation liquid. The gravity stretching process improves the orientation and density of the fiber, avoids the formation of a "skin-core structure", and the obtained special carbon nanotube fiber has better strength performance. In a specific embodiment, the concentration of hydrogen peroxide in the mixed solution is 15-17 wt %, the concentration of potassium permanganate aqueous solution is 15-17 wt %, and the concentration of chlorosulfonic acid solution is 95-99 wt %.

[0008] By adopting the above scheme, the purity of the carbon nanotubes is high, they do not agglomerate under the components of the present application, and are evenly dispersed. The strength of the carbon nanotubes is not greatly lost, and the prepared fiber has high strength.

[0009] In a specific embodiment, the extrusion rate of the spinning solution stream is 0.08-0.10 ml / min, the extrusion height is 20-22 cm, the winding speed is 140-160 mm / s, the soaking time is 20-22 min, the vacuum drying temperature is 110-130° C., and the drying time is 2.5-3.5 h.

[0010] By adopting the above scheme, by limiting the extrusion height and rate, the process parameters are suitable for the spinning solution components of the present application, the air section height is greater than the length of the liquid flow expansion, the velocity gradient of the axial deformation of the spinning solution flow is small, no large deformation occurs, the tension is small, the spinning solution is not easy to break and overflow, the spinning process is uniform and continuous, the obtained fiber structure is stable, the strength is uniform, and it is not easy to break. The obtained fiber is more uniform and dense, has better strength performance, and is smoother. The winding speed of the winding is appropriate, the structure of the fiber is stable, the residual chlorosulfonic acid and butanone on the surface after soaking are fully cleaned, and the drying temperature does not destroy the strength and structure of the fiber.

[0011] In a specific embodiment, the specialty carbon nanotube fibers have a diameter of 7-8 μm.

[0012] By adopting the above scheme, the fibers have high orientation, good density and high strength, and the produced photovoltaic screen has high stability in use.

[0013] In a specific embodiment, the surface coating method is one of electroplating, CVD, PECVD, FCCVD, and coating, and the surface coating material is one or more of nickel, tungsten, and nickel-tungsten alloy.

[0014] By adopting the above scheme, the strength, wear resistance, ink passing rate, etc. of the fiber are further enhanced, and the obtained roll photovoltaic screen printing effect is good.

[0015] In a specific embodiment, the surface coating is nickel electroplating, and the coating process includes: passing the carbon nanotube fiber through a nickel sulfamate electroplating solution with a current density of 0.5A-0.7 / dm 2 , electroplating time 30-35s.

[0016] By adopting the above scheme, a layer of metal nickel with a thickness of 50-100 nm can be electroplated on the fiber surface, which is suitable for the fiber size prepared in this application and has a good effect on improving the strength.

[0017] In a specific embodiment, the carbon nanotube fiber is subjected to plasma treatment, and the treatment steps include: treating the surface of the special carbon nanotube fiber with 30% oxygen and 70% argon low-temperature plasma at 400V voltage and 5Pa pressure for 2-3min, then washing with deionized water and drying.

[0018] By adopting the above scheme, after plasma treatment, the fiber has higher surface activity, better electroplating effect and higher strength.

[0019] In a specific embodiment, the carbon nanotubes are multi-walled carbon nanotubes with a length of 5-15 μm and a diameter of 1-10 nm.

[0020] By adopting the above scheme, compared with single-walled carbon nanotubes, multi-walled carbon nanotubes have higher uniformity and consistency, and the size obtained is more uniform. At the same time, the tube wall is covered with small hole-like defects, and the larger specific surface area makes it more stable to combine with the spinning solution matrix. By selecting multi-walled carbon nanotubes to prepare the spinning solution, the effective contact area between the carbon nanotubes inside the fiber is further improved, and the strength and toughness of the fiber are improved. The obtained fiber and photovoltaic screen have high strength, smooth surface, and stable use. By limiting the size of the carbon nanotubes, it is suitable for the mixed solution and spinning solution concentration of this application. After being treated with hydrogen peroxide and potassium permanganate aqueous solution of this application, there is no significant loss in strength. It is evenly distributed in the spinning solution of this application. After extrusion, it can rely on gravity to form a good orientation, and the gravity will not be too large to make the internal structure uneven. It is suitable for the extrusion height of this application, and the orientation can be completed before entering the coagulation liquid. The obtained fiber has high strength, smoothness and stability.

[0021] In a specific embodiment, the spinning solution also includes graphene, and the particle size of the graphene is 4-10 μm.

[0022] Graphene has high strength and a unique two-dimensional network structure. By adding a certain amount of graphene and limiting the particle size, the graphene is evenly filled in the gaps between the carbon nanotubes of the fiber. Under the action of gravity, it cooperates with the multi-walled carbon nanotubes to form a better orientation, a smoother surface, and a more optimized internal structure of the fiber. When the fiber is subjected to external stress, it can better disperse the stress, and the resulting screen is more stable and less likely to explode.

[0023] In a specific embodiment, the mass ratio of multi-walled carbon nanotubes to graphene is (8-10):1.

[0024] By adopting the above scheme, the mass ratio of multi-walled carbon nanotubes and graphene is limited. At this time, the multi-walled carbon nanotubes and graphene within the size limit of the present application adjust their orientation successively during the spinning process. The graphene with a lamellar structure can better fill the gaps inside the fiber under the steering of the larger-sized multi-walled carbon nanotubes, further optimizing the internal structure of the fiber, and the strength of the obtained fiber is better.

[0025] In summary, this application has the following beneficial effects: 1. Compared with the prior art, the present application realizes large-scale preparation of carbon nanotube fibers by dry-jet wet spinning and using gravity to adjust the orientation of carbon nanotubes. By optimizing the spinning process parameters and limiting the size of the carbon nanotubes, the high orientation of the fibers is ensured, while the density and uniformity of the fiber diameter are improved. The screen made of the fibers can achieve clear and stable printing.

[0026] 2. The present application further improves the strength of the fiber by electroplating the fiber, especially by first plasma treatment and then electroplating, and by limiting the process parameters during the process.

[0027] 3. The present application limits the carbon nanotubes to multi-walled carbon nanotubes, further reduces their size, and further adds graphene of a certain size and mass ratio. The carbon nanotubes in the obtained fibers have better orientation, a smoother surface, and a better internal interlaced structure. When the fibers are subjected to external stress, the stress can be better dispersed, and the obtained screen is more stable and less prone to explosion. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a schematic diagram of the preparation process of the special carbon nanotube fiber of the present application;

[0029] Figure 2 It is a schematic diagram of the preparation process of the special carbon nanotube fiber of the present application;

[0030] Figure 3 It is a schematic diagram of a screen printing mesh made of carbon nanotube fibers and carbon nanotube-graphene composite fibers added with graphene prepared in the present application; Figure 4 It is a schematic diagram of the structure of the screen printing screen plate prepared by the special carbon nanotube fibers of the present application.

[0031] Explanation of the reference numerals: 1: spinning solution; 2: filament; 3: coagulation bath; 4: guide roller; 5: multi-walled carbon nanotube fiber; 6: plating solution. DETAILED DESCRIPTION

[0032] To further help understand the technical solution of the present invention, several specific embodiments are provided to describe the technical solution of the present invention in more detail. All the embodiments described are only partial embodiments of the present invention, not all of them; the embodiments can be combined with each other, and the same or similar concepts or processes may not be described in detail in some embodiments. The following embodiments are further explanations of the present invention, and the present invention is not limited thereto.

[0033] The components of the preparation examples used in the examples of the present application all refer to components obtained by the preparation examples. The experimental reagents in the examples and comparative examples, unless otherwise specified, are conventional commercial brands or obtained by conventional preparation processes. Example

[0034] Example Example 1 S1: 100 mg of multi-walled carbon nanotubes with a length of 10 μm and a diameter of 5 nm were added to 400 mL of a mixed aqueous solution of 15 wt% hydrogen peroxide and 15 wt% potassium permanganate, and then 80 ml of a 2 wt% polytetrafluoroethylene emulsion was added, and magnetic stirring was performed at a speed of 600 r / min, and the mixture was filtered and dried to obtain pretreated multi-walled carbon nanotubes, and then 4.2 g of a 97 wt% chlorosulfonic acid solution was added to the pretreated carbon nanotubes, and the mixture was stirred to obtain a carbon nanotube liquid crystal spinning solution; S2: The carbon nanotube liquid crystal spinning solution prepared in S1 is injected into the air in a vertical direction to extrude a thin stream of the spinning solution, the extrusion rate is 0.08 ml / min, the air section height is 20 cm, and then enters a butanone coagulation bath, is stretched by a winding device, is collected and then immersed in ethanol, filtered, and vacuum dried at 120°C for 3 hours to obtain carbon nanotube fibers with a diameter of 8 μm; S3: The carbon nanotube fibers prepared in S2 are passed through 80 g of nickel sulfamate electroplating solution at a current density of 0.5 A / dm 2 , the electroplating time is 30s, and a layer of metal nickel is electroplated on the surface to obtain special carbon nanotube fibers.

[0035] Example 2 S1: 100 mg of multi-walled carbon nanotubes with a length of 30 μm and a diameter of 15 nm were added to 400 mL of a mixed aqueous solution of 15 wt% hydrogen peroxide and 15 wt% potassium permanganate, and then 80 ml of a 2 wt% polytetrafluoroethylene emulsion was added, and magnetic stirring was performed at a speed of 600 r / min, and the mixture was filtered and dried to obtain pretreated multi-walled carbon nanotubes, and then 4.2 g of a 97 wt% chlorosulfonic acid solution was added to the pretreated carbon nanotubes, and the mixture was stirred to obtain a carbon nanotube liquid crystal spinning solution; S2: The carbon nanotube liquid crystal spinning solution prepared in S1 is injected into the air in a vertical direction to extrude a thin stream of the spinning solution, the extrusion rate is 0.08 ml / min, the air section height is 20 cm, and then enters a butanone coagulation bath, is stretched by a winding device, is collected and then immersed in ethanol, filtered, and vacuum dried at 120°C for 3 hours to obtain carbon nanotube fibers with a diameter of 8 μm; S3: The carbon nanotube fibers prepared in S2 are passed through 80 g of nickel sulfamate electroplating solution at a current density of 0.5 A / dm 2 , the electroplating time is 30s, and a layer of metal nickel is electroplated on the surface to obtain special carbon nanotube fibers.

[0036] Example 3 S1: 100 mg of multi-walled carbon nanotubes with a length of 10 μm and a diameter of 5 nm were added to 400 mL of a mixed aqueous solution of 15 wt% hydrogen peroxide and 15 wt% potassium permanganate, and then 80 ml of a 2 wt% polytetrafluoroethylene emulsion was added, and magnetic stirring was performed at a speed of 600 r / min, and the mixture was filtered and dried to obtain pretreated multi-walled carbon nanotubes, and then 4.2 g of a 97 wt% chlorosulfonic acid solution was added to the pretreated carbon nanotubes, and the mixture was stirred to obtain a carbon nanotube liquid crystal spinning solution; S2: The carbon nanotube liquid crystal spinning solution prepared in S1 is injected into the air in a vertical direction to extrude a thin stream of the spinning solution, the extrusion rate is 0.15 ml / min, the air section height is 20 cm, and then enters a butanone coagulation bath, is stretched by a winding device, is collected and then immersed in ethanol, filtered, and vacuum dried at 120°C for 3 hours to obtain carbon nanotube fibers with a diameter of 8 μm; S3: The carbon nanotube fibers prepared in S2 are passed through 80 g of nickel sulfamate electroplating solution at a current density of 0.5 A / dm 2 , the electroplating time is 30s, and a layer of metal nickel is electroplated on the surface to obtain special carbon nanotube fibers.

[0037] Example 4 S1: 100 mg of multi-walled carbon nanotubes with a length of 10 μm and a diameter of 5 nm were added to 400 mL of a mixed aqueous solution of 15 wt% hydrogen peroxide and 15 wt% potassium permanganate, and then 80 ml of a 2 wt% polytetrafluoroethylene emulsion was added, and magnetic stirring was performed at a speed of 600 r / min, and the mixture was filtered and dried to obtain pretreated multi-walled carbon nanotubes, and then 4.2 g of a 97 wt% chlorosulfonic acid solution was added to the pretreated carbon nanotubes, and the mixture was stirred to obtain a carbon nanotube liquid crystal spinning solution; S2: The carbon nanotube liquid crystal spinning solution prepared in S1 is injected into the air in a vertical direction to extrude a thin stream of the spinning solution, the extrusion rate is 0.08 ml / min, the air section height is 30 cm, and then enters a butanone coagulation bath, is stretched by a winding device, is collected and then immersed in ethanol, filtered, and vacuum dried at 120°C for 3 hours to obtain carbon nanotube fibers with a diameter of 8 μm; S3: The carbon nanotube fibers prepared in S2 are passed through 80 g of nickel sulfamate electroplating solution at a current density of 0.5 A / dm 2 , the electroplating time is 30s, and a layer of metal nickel is electroplated on the surface to obtain special carbon nanotube fibers.

[0038] Example 5 S1: 100 mg of multi-walled carbon nanotubes with a length of 10 μm and a diameter of 5 nm were added to 400 mL of a mixed aqueous solution of 15 wt% hydrogen peroxide and 15 wt% potassium permanganate, and then 80 ml of a 2 wt% polytetrafluoroethylene emulsion was added, and magnetic stirring was performed at a speed of 600 r / min, and the mixture was filtered and dried to obtain pretreated multi-walled carbon nanotubes, and then 4.2 g of a 97 wt% chlorosulfonic acid solution was added to the pretreated carbon nanotubes, and the mixture was stirred to obtain a carbon nanotube liquid crystal spinning solution; S2: The carbon nanotube liquid crystal spinning solution prepared in S1 is injected into the air in a vertical direction to extrude a thin stream of the spinning solution, the extrusion rate is 0.08 ml / min, the air section height is 20 cm, and then enters a butanone coagulation bath, is stretched by a winding device, is collected and then immersed in ethanol, filtered, and vacuum dried at 120°C for 3 hours to obtain carbon nanotube fibers with a diameter of 8 μm; S3: The carbon nanotube fibers prepared in S2 are passed through 80 g of nickel sulfamate electroplating solution at a current density of 1.0 A / dm 2 , the electroplating time is 30s, and a layer of metal nickel is electroplated on the surface to obtain special carbon nanotube fibers.

[0039] Example 6 S1: 100 mg of multi-walled carbon nanotubes with a length of 10 μm and a diameter of 5 nm were added to 400 mL of a mixed aqueous solution of 15 wt% hydrogen peroxide and 15 wt% potassium permanganate, and then 80 ml of a 2 wt% polytetrafluoroethylene emulsion was added, and magnetic stirring was performed at a speed of 600 r / min, and the mixture was filtered and dried to obtain pretreated multi-walled carbon nanotubes, and then 4.2 g of a 97 wt% chlorosulfonic acid solution was added to the pretreated carbon nanotubes, and the mixture was stirred to obtain a carbon nanotube liquid crystal spinning solution; S2: The carbon nanotube liquid crystal spinning solution prepared in S1 is injected into the air in a vertical direction to extrude a thin stream of the spinning solution, the extrusion rate is 0.08 ml / min, the air section height is 20 cm, and then enters a butanone coagulation bath, is stretched by a winding device, is collected and then immersed in ethanol, filtered, and vacuum dried at 120°C for 3 hours to obtain carbon nanotube fibers with a diameter of 8 μm; S3: The surface of the carbon nanotube fiber was treated with 30% oxygen and 70% argon low-temperature plasma at 400 V and 5 Pa for 2 min, then washed with deionized water and dried; S4: The plasma-treated carbon nanotube fibers prepared in S3 were passed through 80 g of nickel sulfamate electroplating solution at a current density of 0.5 A / dm 2 , the electroplating time is 30s, and a layer of metal nickel is electroplated on the surface to obtain special carbon nanotube fibers.

[0040] Example 7 S1: 90 mg of multi-walled carbon nanotubes with a length of 10 μm and a diameter of 5 nm and 10 mg of graphene with an average particle size of 5 μm were added to 400 mL of a mixed aqueous solution of 15 wt% hydrogen peroxide and 15 wt% potassium permanganate, and then 80 ml of a 2 wt% polytetrafluoroethylene emulsion was added, and magnetic stirring was performed at a speed of 600 r / min, and the mixture was filtered and dried to obtain pretreated multi-walled carbon nanotubes, and then 4.2 g of a 97 wt% chlorosulfonic acid solution was added to the pretreated carbon nanotubes, and the mixture was stirred to obtain a carbon nanotube liquid crystal spinning solution; S2: The carbon nanotube liquid crystal spinning solution prepared in S1 is injected into the air in a vertical direction to extrude a thin stream of the spinning solution, the extrusion rate is 0.08 ml / min, the air section height is 20 cm, and then enters a butanone coagulation bath, is stretched by a winding device, is collected and then immersed in ethanol, filtered, and vacuum dried at 120°C for 3 hours to obtain carbon nanotube fibers with a diameter of 8 μm; S3: The surface of the carbon nanotube fiber was treated with 30% oxygen and 70% argon low-temperature plasma at 400 V and 5 Pa for 2 min, then washed with deionized water and dried; S4: The plasma-treated carbon nanotube fibers prepared in S3 were passed through 80 g of nickel sulfamate electroplating solution at a current density of 0.5 A / dm 2 , the electroplating time is 30s, and a layer of metal nickel is electroplated on the surface to obtain special carbon nanotube fibers.

[0041] Example 8 S1: 70 mg of multi-walled carbon nanotubes with a length of 10 μm and a diameter of 5 nm and 30 mg of graphene with an average particle size of 5 μm were added to 400 mL of a mixed aqueous solution of 15 wt% hydrogen peroxide and 15 wt% potassium permanganate, and then 80 ml of a 2 wt% polytetrafluoroethylene emulsion was added, and magnetic stirring was performed at a speed of 600 r / min, and the mixture was filtered and dried to obtain pretreated multi-walled carbon nanotubes, and then 4.2 g of a 97 wt% chlorosulfonic acid solution was added to the pretreated carbon nanotubes, and the mixture was stirred to obtain a carbon nanotube liquid crystal spinning solution; S2: The carbon nanotube liquid crystal spinning solution prepared in S1 is injected into the air in a vertical direction to extrude a thin stream of the spinning solution, the extrusion rate is 0.08 ml / min, the air section height is 20 cm, and then enters a butanone coagulation bath, is stretched by a winding device, is collected and then immersed in ethanol, filtered, and vacuum dried at 120°C for 3 hours to obtain carbon nanotube fibers with a diameter of 8 μm; S3: The surface of the carbon nanotube fiber was treated with 30% oxygen and 70% argon low-temperature plasma at 400 V and 5 Pa for 2 min, then washed with deionized water and dried; S4: The plasma-treated carbon nanotube fibers prepared in S3 were passed through 80 g of nickel sulfamate electroplating solution at a current density of 0.5 A / dm 2 , the electroplating time is 30s, and a layer of metal nickel is electroplated on the surface to obtain special carbon nanotube fibers.

[0042] Example 9 S1: stretching the net: plain weaving the special carbon nanotube fibers prepared in Example 1 to obtain a special carbon nanotube fiber net, and then sticking it at a position of 600mm*600mm with an adhesive according to a certain tension requirement; S2: Compounding: The PE hot melt adhesive film is compounded on the steel wire mesh on the special carbon nanotube fiber mesh at about 100° C. in a compounding machine, and the special carbon nanotube fiber mesh in the middle is removed to obtain a false frame screen; S3: Top frame: The composite false frame screen is placed on the fixture, and the top frame machine uses a certain air pressure to push the 450mm*450mm main frame to the center of the false frame, and then adheres it with adhesive to form a 450mm*450mm main frame screen; S4: Degreasing: Use cleaning agent to wipe and clean the screen of this frame; S5: Wire drawing: Cutting part of the steel wire with laser; S6: Degreasing: Wipe and clean with a cleaning agent; S7: bonding: coating the polyimide film with adhesive and pressing it on the center of the steel mesh at a temperature of 200°C; S8: The photosensitive adhesive covers the area outside the pattern to prevent ink leakage at the edge of the wire mesh; S9: Graphics: Through graphic conversion, the polyimide film is cut by laser to form a pattern; S10: The formed screen is packaged with tapes of various specifications to achieve the effects of wear resistance, protection and ink blocking.

[0043] Comparative Example Comparative Example 1 S1: 100 mg of multi-walled carbon nanotubes with a length of 10 μm and a diameter of 5 nm were added to 400 mL of a mixed aqueous solution of 15 wt% hydrogen peroxide and 15 wt% potassium permanganate, and then 80 ml of a 2 wt% polytetrafluoroethylene emulsion was added, and magnetic stirring was performed at a speed of 600 r / min, and the mixture was filtered and dried to obtain pretreated multi-walled carbon nanotubes, and then 4.2 g of a 97 wt% chlorosulfonic acid solution was added to the pretreated carbon nanotubes, and the mixture was stirred to obtain a carbon nanotube liquid crystal spinning solution; S2: The carbon nanotube liquid crystal spinning solution prepared in S1 was directly extruded into a butanone coagulation bath at an extrusion rate of 0.08 ml / min, stretched by a winding device, collected and then immersed in ethanol, filtered, and vacuum dried at 120°C for 3 hours to obtain carbon nanotube fibers with a diameter of 8 μm; S3: The carbon nanotube fibers prepared in S2 are passed through 80 g of nickel sulfamate electroplating solution at a current density of 0.5 A / dm 2 , the electroplating time is 30s, and a layer of metal nickel is electroplated on the surface to obtain special carbon nanotube fibers.

[0044] Performance testing The photovoltaic screen was prepared according to the following steps and then tested.

[0045] Test 1: The tensile strength 1 of the fibers prepared in each embodiment and comparative example was tested. The test results are summarized in Table 1.

[0046] Test 2: The fibers prepared in each embodiment and comparative example were immersed in the ink Merida UV 9000 for 10 hours, and then the tensile strength 2 of the adhesive prepared in each embodiment and comparative example was detected, and the tensile strength retention rate was calculated. The calculation method was: tensile strength 2 / tensile strength 1×100%. The test results are summarized in Table 1.

[0047] Test 3: Use the photovoltaic screen made of the special carbon nanotubes prepared in this application for screen printing, observe the printing clarity, and rate it on a scale of 1-5, where 1 is very clear and 5 is very unclear. The rating results are summarized in Table 1.

[0048] Table 1 Tensile strength (GPa) Tensile strength retention rate (%) Clarity level Example 1 4.9 96.4 2 Example 2 4.3 91.0 3 Example 3 4.3 90.2 4 Example 4 4.0 93.5 3 Example 5 4.9 96.6 3 Example 6 5.1 96.7 1 Example 7 5.3 97.4 1 Example 8 5.1 96.8 2 Comparative Example 1 1.8 65.1 5 In combination with Examples 1-4, Comparative Example 1 and Table 1, the present application uses dry-jet wet spinning and optimizes spinning process parameters, limits the size of carbon nanotubes, and uses gravity to adjust the orientation of carbon nanotubes, so that the fibers are dense and uniform.

[0049] In combination with Example 1, Examples 5-6 and Table 1, the present application further improves the strength of the fiber by electroplating the fiber, especially first plasma treatment and then electroplating treatment, and limits the process parameters in the process. The fiber surface is smooth and the strength is well retained in the solvent.

[0050] In combination with Example 1, Examples 6-8 and Table 1, the present application limits the carbon nanotubes to multi-walled carbon nanotubes, further adds graphene of a certain size and mass ratio, and the carbon nanotubes in the prepared fibers have better orientation, better interlacing structure inside the fibers, and better strength and solvent resistance.

[0051] This specific embodiment of the present application is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, a person skilled in the art may make modifications to the embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for preparing special carbon nanotube fibers for high-performance photovoltaic screens, characterized in that: The steps include: S1: adding carbon nanotubes to a mixed solution of hydrogen peroxide and potassium permanganate, then adding polytetrafluoroethylene emulsion, magnetically stirring, filtering, and drying to obtain pretreated multi-walled carbon nanotubes, then adding chlorosulfonic acid solution to the pretreated carbon nanotubes, magnetically stirring, to obtain a carbon nanotube liquid crystal spinning solution; S2: injecting the carbon nanotube liquid crystal spinning solution prepared in S1 into the air in a vertical direction to extrude a thin stream of the spinning solution, and then entering the butanone coagulation bath, and stretching the spinning solution by a winding device, collecting the spinning solution, and then immersing the spinning solution in ethanol, filtering, and vacuum drying to obtain carbon nanotube fibers; S3: coating the surface of the carbon nanotube fiber prepared in S2 to obtain special carbon nanotube fiber; The carbon nanotubes are multi-walled carbon nanotubes with a length of 5-15 μm and a diameter of 1-10 nm; the extrusion rate of the extruded spinning solution stream is 0.08-0.10 ml / min, the extrusion height is 20-22 cm, the winding speed is 140-160 mm / s, the soaking time is 20-22 min, the vacuum drying temperature is 110-130° C., and the drying time is 2.5-3.5 h.

2. The method for preparing special carbon nanotube fibers for high-performance photovoltaic screens according to claim 1, characterized in that: The concentration of hydrogen peroxide in the mixed solution is 15-17wt%, the concentration of potassium permanganate aqueous solution is 15-17wt%, and the concentration of chlorosulfonic acid solution is 95-99wt%.

3. The method for preparing special carbon nanotube fibers for high-performance photovoltaic screens according to claim 1, characterized in that: The diameter of the special carbon nanotube fiber is 7-8 μm.

4. The method for preparing special carbon nanotube fibers for high-performance photovoltaic screens according to claim 1, characterized in that: The surface coating method is one of electroplating, CVD, PECVD, FCCVD, and coating, and the surface coating material is one or more of nickel, tungsten, and nickel-tungsten alloy.

5. The method for preparing special carbon nanotube fibers for high-performance photovoltaic screens according to claim 4, characterized in that: The surface coating is nickel electroplating, and the coating process includes: passing the carbon nanotube fiber through a nickel sulfamate electroplating solution with a current density of 0.5-0.7A / dm 2 , electroplating time 30-35s.

6. The method for preparing special carbon nanotube fibers for high-performance photovoltaic screens according to claim 4, characterized in that: The carbon nanotube fiber is subjected to plasma treatment, and the treatment steps include: treating the surface of the special carbon nanotube fiber with 30% oxygen and 70% argon low-temperature plasma under the conditions of 400V voltage and 5Pa pressure for 2-3min, then washing with deionized water and drying.

7. The method for preparing special carbon nanotube fibers for high-performance photovoltaic screens according to claim 1, characterized in that: The spinning solution also includes graphene, and the particle size of the graphene is 4-10 μm.

8. The method for preparing special carbon nanotube fibers for high-performance photovoltaic screens according to claim 7, characterized in that: The mass ratio of the multi-walled carbon nanotubes to graphene is (8-10):1.